Innovation Capability, Absorptive Capacity, and Collaborative Networks as Determinants of Competitive Advantage in the SME Laundry Sector - Faiz, Rayhan; Isfianadewi, Dessy; Sudrajat, Yusuf (Jurnal EMT KITA, 2026)
Grounded in the Resource-Based View and Dynamic Capabilities Theory, this study examines how internal and relational capabilities shape competitive advantage among small and medium-sized enterprises (SMEs) in the service sector. The research investigates the influence of innovation capability and absorptive capacity on competitive advantage, with collaborative networks tested as a mediating variable. Previous studies have reported inconsistent results regarding these relationships, particularly within resource-constrained SME contexts. To address this gap, data were collected from 113 SME owners and managers in the laundry service industry using a structured questionnaire with a five-point Likert scale. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS to assess both the measurement and structural models. The findings reveal that innovation capability (β = 0.456, p < 0.001) and absorptive capacity (β = 0.439, p < 0.001) significantly enhance competitive advantage. Both variables also positively influence collaborative networks, which in turn have a significant effect on competitive advantage (β = 0.286, p = 0.001). Moreover, collaborative networks partially mediated the relationship between absorptive capacity and competitive advantage (β = 0.109, p = 0.048), but not between innovation capability and competitive advantage (β = 0.141, p = 0.062). These findings confirm that innovation and knowledge absorption are strategic resources that drive competitiveness, while collaboration provides conditional benefits depending on firm capabilities. Managers are encouraged to institutionalize regular customer feedback systems and strengthen partnerships with local suppliers to enhance innovation outcomes. The study clarifies inconsistencies in prior research and provides practical insights for improving SME competitiveness through balanced internal and external capability development.